Comparison of Neuropsychological Functioning among Individuals Diagnosed with Bipolar Disorder with and without Childhood ADHD - Arash Mani; Leila Khabir; Amir Reza Khodaman (Shiraz University of Medical Sciences, 2024)
Background: Bipolar mood disorder (BMD) with a lifetime history of Attention-deficit hyperactivity disorder (ADHD) characterized by a particularly neuropsychological profile. This study aimed to clarify whether there is a difference between BMD patients with ADHD and BMD patients without ADHD in terms of neuropsychological functioning.Methods: This is a cross-sectional study with 68 samples (24 patients had BMD with ADHD and 44 patients had BMD) selected based on the target sampling during a year (March 2014 to March 2015). Tower of London (ToL) task, Conners' Continuous Performance Test (CPT), and Wisconsin Card Sorting Test (WCST) were used for assessing neuropsychological functioning in participants. All statistical analyses were performed using the Statistical Package for the Social Sciences (SPSS) version 16 software.Results: The results revealed that the BMD with ADHD group was not more impaired than the BMD group on two measures of executive functioning TOL and CPT. The BMD in the ADHD group was more impaired than the BMD group on WCST.Conclusion: This study will be effective in understanding whether the cognitive flexibility impairments often detected in adult BMD are partially the result of lifetime ADHD.